Students’ Concept Images on Set: Zone of Differences between Concept Image and Formal Concept Definition - et al., Jamilah (International Journal of Advanced Science and Technology, 2019)
Students’ concept image describes how students interpret a concept. students’ image of concepts should be the same as the formal concept definition. Therefore, an analysis was carried out to reveal the students ’concept images and the zone of differences between students’ concept images and the formal concept definition of the set concepts and set elements. This research is a qualitative research with an interpretive phenomenology approach. There are 28 seventh grade junior high school students participated in this study. The data were collected through questionnaires and interviews. The findings of the study demonstrated that there are 4 categories of students ’concept images in understanding set and three of them have differences with formal concept definition. In addition, there are six categories of students’ concept images in interpreting the concept of set elements from the venn diagram, three of which also have differences with the formal concept definition. This result indicated that there are still many differences that occur between students’ concept images and formal concept definitions.